Malaria transmission through the mosquito requires the function of the OMD protein - Currà, Chiara; Kehrer, Jessica; Lemgruber, Leandro; Silva, Patricia A. G. C.; Bertuccini, Lucia; Superti, Fabiana; Pace, Tomasino; Ponzi, Marta; Frischknecht, Friedrich; Siden-Kiamos, Inga; Mair, Gunnar R. (OncoTarget, 2019)
Ookinetes, one of the motile and invasive forms of the malaria parasite, rely on gliding motility in order to establish an infection in the mosquito host. Here we characterize the protein PBANKA_0407300 which is conserved in the Plasmodium genus but lacks significant similarity to proteins of other eukaryotes. It is expressed in gametocytes and throughout the invasive mosquito stages of P. berghei, but is absent from asexual blood stages. Mutants lacking the protein developed morphologically normal ookinetes that were devoid of productive motility although some stretching movement could be detected. We therefore named the protein Ookinete Motility Deficient (OMD). Several key factors known to be involved in motility however were normally expressed and localized in the mutant. Importantly, the mutant failed to establish an infection in the mosquito which resulted in a total malaria transmission blockade.
Gesehen am 16.04.2020